2019
DOI: 10.3390/geosciences9050212
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Wave Dissipation Rate and Particles Velocity in Muddy Beds

Abstract: The interactions between free surface waves and layers of cohesive sediments including wave height attenuation and mud movement are of great importance in coastal and marine engineering. In this study, the results from a new analytical model were compared with those from literature experimental works and analytical models in terms of wave height dissipation rate and mud velocity. It was found that the new model provided good agreements in the case of coexisting waves and currents, while the literature model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…This is due to the boundary layer assumption made in this study. Shamsnia et al [34] have shown that the models with boundary layer assumptions provided better agreements with the laboratory data with higher values of mud velocities in comparison with all the other models (confirmed in the present study). However, small fluctuations-induced by the mud layer inhomogeneity-and rheological effects could not be considered by the theory.…”
Section: First Test Casesupporting
confidence: 88%
See 2 more Smart Citations
“…This is due to the boundary layer assumption made in this study. Shamsnia et al [34] have shown that the models with boundary layer assumptions provided better agreements with the laboratory data with higher values of mud velocities in comparison with all the other models (confirmed in the present study). However, small fluctuations-induced by the mud layer inhomogeneity-and rheological effects could not be considered by the theory.…”
Section: First Test Casesupporting
confidence: 88%
“…This is because such high mud viscosities result in large boundary layer thicknesses of the mud layer that matches well with the assumptions of the proposed analytical model. (The same conclusion was provided by Shamsnia et al, [34]). It is revealed from the figure that the model provides agreements with the data in the upper layer of mud.…”
Section: First Test Casesupporting
confidence: 86%
See 1 more Smart Citation